Escape passive lectures: an interactive, multi-themed digital escape room on medicinal chemistry topics - Aisyah Saad, Abdul Rahim; Chuah, Kee Man (2022)
During the COVID-19 endemic, delivering synchronous lectures and video lectures in the manner of the traditional lecture method seems to trigger low attendance, hinder peer interactions and encourage passive learning in Generation Z students. To overcome such problems, innovative approaches like game-based learning are often employed. Educational games are widely incorporated into the teaching and learning process to enhance collaboration, critical thinking, and communication skills. An escape room is a type of educational, puzzle-based game that puts student teams in charge of problem-solving scenarios before escaping. Previous studies have shown its effectiveness in providing an overall positive learning experience, though investigations involving pharmacy students in a medicinal chemistry course remain scant. This paper investigates pharmacy students’ perceptions of an interactive, multi-themed medicinal chemistry escape room activity that was employed as an educational intervention in lieu of a synchronous lecture during the COVID-19 pandemic. Third-year pharmacy students positively perceived the multi-themed digital ER game in helping them improve their understanding in medicinal chemistry topics. It has the potential to serve as an educational intervention to escape passivity in the traditional lecture method and enhance students’ autonomy in fostering the acquisition of 21st-century skills.